Releasing time to care: a quality improvement project aimed to increase direct rehabilitation time in a Stroke Rehabilitation Centre - Susan White; Benjamin Jelley; Claire Haddock; Jennifer Blackhouse; Dolores Macchiavello; Jennifer Clark; James Hinder; Amy Joyce; Kate Matchett; Eden Morris; Carys Moss; Chris Rees; et al. (BMJ Open Quality)
Stroke is a leading cause of disability among adults, and any treatment that improves functional outcome, like higher intensity of rehabilitation therapy, can significantly reduce its financial burden. Clinicians on a stroke rehabilitation ward are expected to track and nationally report on rehabilitation time to contribute to the Sentinel Stroke National Audit Programme (SSNAP), a process that was manual, paper-based, time-consuming and redundant, which in turn impacted on a reduction in clinical time to provide stroke rehabilitation. We aimed to release 20% of clinical time by reducing inefficiencies within their time management and reporting process, ensuring that clinicians had more time available for direct patient care. To do so, we developed a tool to gather and analyse SSNAP-specific data and use Kanban cards to make weekly actions visible to reduce miscommunication. As a result, the whole occupational therapists team gained 7.5 hours a month (25% of released time, 12 extra additional therapy sessions available) when improving their data gathering and analysis process. A specialist physiotherapist saw a 2 hour a month gained and 4 hours a month gained for a Physiotherapist. Dietitians also saved 3 hours a month by not having to duplicate information. This process is part of a key organisational requirement for clinical teams working with stroke patients admitted to hospital and by addressing some inefficiencies, we were able to impact on direct patient care.